C07 Exploring purposeful outdoor physical activity and mindfulness for wellbeing: a practitioners' perspective - Lawley, Becky; Chandler, Charlotte (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Mindfulness training can improve one's capacity for self-regulation, including attentional processes, behaviour, and mood control (Tang, Hölzel & Posner, 2015, Nature Rev Neurosci, 16, 213-225). Green exercise has been shown to enhance both physiological and mental health measures with all populations, including adults with long-term diseases or mental health problems, benefiting from outdoor, nature-based interventions (Coventry et al., 2021, Pop Health, 16, 100934; Pretty, Peacock, Sellens & Griffin, 2005, Int J Health Res, 15, 319-337). Engaging in outdoor activities and developing an affective relationship with nature is a key mechanism on the path to wellbeing benefits that go beyond the advantages of simply visiting or being in nature (Richardson & McEwan, 2018, Front Psych, 9, 1500). The aim of the study is to gain insight into how purposeful outdoor physical activity can be used as a form of mindfulness and its potential impact on wellbeing from a practitioner’s perspective. 6-8 exercise professionals aged 18 and over, who have sufficient knowledge of exercise and wellbeing, for example exercise psychologists or health and wellbeing coaches will be recruited for this study. Recruitment for this study will take place by word of mouth and contact directly through a company or LinkedIn. Exercise psychologists must be BASES or BPS accredited. Data will be collected through interviews either at a location to suit the participant or remote (over Microsoft Teams) and analysed using thematic analysis. Interviews will be recorded using the voice memos app on an iPhone and then written up using the dictate function on Microsoft Word. Information collected in addition to the interview will be, participants sex and job title, including how long they have been in their position for. Interviews with each participant will include the following topic areas; discussion around their job and experiences so far within their job, outdoor physical activity and what it means to them, challenges or barriers they have observed from working with clients around physical activity, exploring their opinions on outdoor physical activity in green space, personal experiences being physically active in green space, self-development as a practitioner in the exercise psychology or health and wellbeing and any future recommendations for either other practitioners to think about when working with clients or individuals to think about when trying to include green space in their current physical activity routines.